Stem cell transplantation – an overview of clinic-based data and practice in the era of new drugs - Todorović Balint, Milena; Vraneš, Marija; Pavlović, Mirjana; Šerbić, Olivera; Pešić, Andrej; Lazović, Aleksandar; Balint, Bela (Vojnosanitetski pregled, 2026)
Hematopoietic stem cell transplantation (HSCT) has been the therapy of choice for treating some hematologic malignancies and selected non-malignant disorders for decades. With the introduction of novel immunotherapeutic and cell-mediated approaches, the role of autologous HSCT (auto-HSCT) and allogeneic HSCT (allo-HSCT) should be redefined. Auto-HSCT remains the standard of treatment for multiple myeloma, Hodgkin’s lymphoma, and non-Hodgkin’s lymphoma. The use of novel agents, including proteasome inhibitors, immunomodulatory drugs, monoclonal and bispecific antibodies, enhances the intensity and efficacy of the therapeutic response and opens debate on an optimized timing for HSCT. Allo-HSCT represents the most effective type of adoptive immunotherapy, ensuring complete and long-term hematopoietic reconstitution, often accompanied by the graft-versus-leukemia effect. It remains the main curative treatment for acute leukemias, high-risk myelodysplastic and myeloproliferative syndromes, and severe aplastic anemia. Improvements in stem cell (SC) donor selection, ex vivo manipulations of harvested cells, and graft engineering with superior immune monitoring have broadened and expanded their applicability, while improving safety and clinical outcome. Despite rapid progress in cellular and other immunotherapies, HSCT continues to play an essential role in the treatment of numerous hematologic disorders. A combination of HSCT with novel drugs and other immunotherapies offers the potential for personalized and safer treatment with long-term positive clinical outcomes, ensuring that HSCT remains a highly relevant method in modern medicine. The aim of this review was to summarize current biological concepts of SCs, as well as important advances in the rapidly developing fields of SC research, and to determine the place and efficacy of HSCT nowadays, in the era of new therapeutic approaches and agents.
Keywords: allografts; cryopreservation; hematologic diseases; immunotherapy; multiple myeloma; stem cells; transplantation, autologous.